30 A case control study of percutaneous coronary intervention in spontaneous coronary artery dissection. (17th July 2020) - Kotecha, Deevia; Premawardhana, Amila Diluka; Garcia-Guimaraes, Marcos; Pellegrini, Dario; Ziaullah, Jan; Bastante, Teresa; Wood, Alice; Maas, Angela; Van Geuns, Robert Jan; Alfonso, Fernando; Adlam, David
Abstract : Background: Spontaneous Coronary Artery Dissection (SCAD) has emerged as an important cause of acute coronary syndrome (ACS) particularly in young-middle aged women. The mechanism of coronary obstruction, acute vessel response to percutaneous coronary intervention (PCI) and natural course of conservatively managed lesions differs significantly in SCAD when compared with atherosclerotic ACS. Revascularization is challenging due to an underlying disrupted and friable coronary vessel wall leading to widely reported worse outcomes than for atherosclerotic coronary disease. Therefore, a conservative approach where possible is favoured however in some cases haemodynamic instability, ongoing ischaemia and reduced distal flow mandates consideration of revascularization. Purpose: To compare SCAD survivors managed with PCI or conservatively in terms of presentation characteristics, complications and long-term outcomes. Methodology and Results: Two hundred and twenty-five angiographically confirmed SCAD survivors (95% female, 47±9.7yrs) who underwent PCI were compared in a case control study with two hundred and twenty-five angiographically confirmed SCAD survivors (92% female, 49±9.9yrs) who were conservatively managed. Patients were recruited from UK, Spanish and Dutch SCAD registries and both groups were well matched in terms of baseline demographics. Those treated with PCI were more likely to present with proximal SCAD (30.8% vs 7.6% P<0.01) and ST elevation myocardial infarction (STEMI) or cardiac arrest with reduced flow (32.3% vs 6.3% P<0.01). Intervention was performed with stents in 72.4%, plain old balloon angioplasty in 21.1% and wiring in 6.4% of cases and more often for multi-segment disease (40.8% vs 26.3% P<0.01). In cases with initial reduced flow undergoing PCI an improvement in flow was seen in 83%. Analysis of all cases reveal complications in 85 (38.8%). SCAD lesion length was associated with presence of complications (P=0.025). However, when assessed for the clinical significance of that complication (defined by a reduction in flow in a proximal/mid vessel, stent extension into left main stem, iatrogenic dissection requiring PCI and CABG as a consequence of PCI), only 26 cases (11.6%) met seriousness criteria with iatrogenic dissection accounting for nearly half (44.6%). There was a non-significant trend towards major adverse cardiovascular events (MACE) occurring more frequently in those undergoing PCI (18 % vs 11% P=0.067) driven by revascularisation (5% vs 1% P=0.036). Median follow up was 2.7 years. Conclusions: PCI in SCAD is most often performed in higher risk cases. Whilst overall complication rates were similar to those widely reported, clinically significant complications were uncommon and most interventions in this context were associated with improved angiographic endpoints. Conflict of Interest: NA